The organization of accounting and public audit in budget organizations - Тулегенова, Р. (Journal of Economic Research & Business Administration, 2017)
This article discusses the procedure for the organization of accounting and public audit in budget organizations. Government agencies provide a timely presentation of budget programs administrators, as well as the correctness of the conclusion of the financial plans. Accounting of budgetary organizations shall be used under the laws of the Republic of Kazakhstan. Particularlly, in the process of putting the cost estimates of enterprises, organizations and individuals, as well as a common position and cash settlements for monitoring the compliance of inventories and government agencies including the complete and accurate information. The objective of public audit is to improve the management and efficient use of budget funds, the state assets and entities of quasi-public sector organizations.